The level of emotional maturity and moral bedhaviours - Strus, Włodzimierz (Studia Psychologica: Theoria et praxis, 2006)
This article presents problem of a relationship between the level of the most important features of emotional maturity and exacerbation of chosen moral behaviors. The dependencies were analysed among emotional stability, strength of character, emotional sensibility, selfcontrol and veracity, helping others, keeping the promises regarding different categories of people. The research group consisted of 73 students (34 men and 39 women). The results indicate to the positive correlations between self-control, strength of character and dimensions of veracity and keeping promises. In case of emotional stability, the sensibility and helping others a few only dependencies were affirmed. Additionally the analysis has also shown essential sexual differences.